Anti-inflammatory potential of african leaf water extract - Agus Setiani, Lusi; Rusli, Zaldi (Journal of Agriculture and Applied Biology, 2020)
Inflammation is the immune system's main response to infection and irritation. African leaf (Gymnanthemum amygdalinum) is one of the medicinal plants that can be used as anti-inflammatory because of the presence of flavonoid compounds. Flavonoid compounds have an anti-inflammatory effect that can regulate arachidonic acid metabo-lism by inhibiting cyclooxygenase (COX) and lipooksigenase activi-ties. This study aims to obtain scientific information and the potential of African leaf extract as an anti-inflammatory in vitro and in vivo test. In this study, in vitro and in vivo anti-inflammatory activity tests were carried out. The in vitro anti-inflammatory activity was evaluated by the ability of African leaf extracts to prevent protein denaturation and in vivo anti-inflammatory activity by observing the reduction of edema in the soles of rats induced by carrageenan by giving three lev-els of doses of African leaf extract. The results showed that the African leaf extract at a concentration of 8273.91 mg L-1 was able to inhibit 50% denatured protein (IC50), while in the in vivo test African leaf had the potential as an anti-inflammatory with the most effective percent-age of inhibition at a dose of 200 mg kg-1 which is 85.20%. African leaf have the potential of approximately 2 times greater than the positive control of diclofenac sodium which is 45.70%.